The Meaning of Place and the Edu-Tourist Experience in Wot Batu Bandung, Indonesia - QOMARUZZAMAN, Bambang; RAHMAN, M. Taufiq (Journal of Environmental Management and Tourism; Vol 10 No 8 (2019): JEMT Volume X Issue 8(40) Winter 2019DO - 10.14505//jemt.10.8(40).14, 2020)
Meaning is the most important psychological aspect of an activity carried out by a group of people to look for values and benefits in an activity. The meaning really determines the use value, direction and orientation of activities. Because the meaning is very important position then analyzing the meaning of an art activity becomes an important study as well. This study traces the meaning of the conditions and activities of one of the recreation areas in the city of Bandung both the meaning for the initiators and for the visitors. This article will analyze their existence from the phenomenological approach. The phenomenological approach aims to understand human’s existence and their role in the society. This research found that the meaning of recreational activities felt by those involved there are the feelings of peaceful, quiet life, summoning the soul, spiritual nature and the enjoyment of thought.